Anti-vaccination and pro-CAM attitudes both reflect magical beliefs about health. Issue 9 (21st February 2018) - Bryden, Gabrielle M.; Browne, Matthew; Rockloff, Matthew; Unsworth, Carolyn
Highlights: No evidence that vaccine scepticism is due to CAM practitioners influencing their clients. Magical health belief was by far the strongest predictor of both CAM and vaccination attitudes. Holistic health belief was also a predictor of both CAM and vaccination attitudes. Abstract: We examined the relationship between complementary and alternative medicine (CAM) use and vaccination scepticism; and specifically whether a person's more general health-related worldview might explain this relationship. A cross-sectional online survey of adult Australians (N = 2697) included demographic, CAM, and vaccination measures, as well as the holistic and magical health belief scales (HHB, MHB). HHB emphasises links between mind and body health, and the impact of general 'wellness' on specific ailments or resistance to disease, whilst MHB specifically taps ontological confusions and cognitive errors about health. CAM and anti-vaccination were found to be linked primarily at the attitudinal level (r = −0.437). We did not find evidence that this was due to CAM practitioners influencing their clients. Applying a path-analytic approach, we found that individuals' health worldview (HHB and MHB) accounted for a significant proportion (43.1%) of the covariance between CAM and vaccination attitudes. MHB was by far the strongest predictor of both CAM and vaccination attitudes in regressions including demographic predictors. We conclude that vaccination scepticism reflects part of a broader health worldview that discounts scientific knowledge in favour of magical or superstitious thinking. Therefore, persuasive messages reflecting this worldview may be more effective than fact-based campaigns in influencing vaccine sceptics.